Cultural adaptation to Brazil of the questionnaire Costs of caring for children with cancer - Raquel Pan; Amanda Rossi Marques; Bruna Domingos dos Santos; Eufemia Jacob; Claudia Benedita dos Santos; Lucila Castanheira Nascimento (Universidade de São Paulo, 2014)
OBJECTIVE: to present the cultural adaptation of the questionnaire Costs of caring for children with cancer, offering a valid and reliable tool to assess the economic repercussions of childhood cancer for Brazilian families.METHOD: it is a methodological research with a cross-sectional design. The methodological framework to validate the questionnaire was a combined process that included seven steps: translation to Portuguese; first translated consensus version; evaluation by Expert Committee; consensus on the Expert Committee version; back-translation; consensus of back-translated versions; semantic validation. The study was conducted in two phases: phase one was the translation and back-translations process, with five expert committee members. Phase two was the semantic validation, with 24 participants, who answered an instrument about their impressions of the questionnaire and suggested modifications.RESULTS: in phase one, items were included, excluded, and replaced to make the content equivalent and valid for use with Brazilian context. In phase two, the majority of the participants were mothers, who made suggestions about the relevance and clarity of the items in the questionnaire.CONCLUSIONS: the authors discussed these recommendations and made adaptations, turning the questionnaire into a valid and reliable tool for application.